The past and the present use of traditional herbal medicine - Ismail, Azlini (Microcredential @ IIUM, 2022)
This article gives a general insight into the past and present use of traditional herbal medicine. It covers definitions, traditional and latest methods of preparation for use, its historical use in various traditional medicinal practices, commercial drugs derived from traditional medicinal herbs, and the recent increasing trend of use for homemade medicinal preparations and commercial herbal products in the market.